Paradigma Islam Dalam Kewajiban Menuntut Ilmu Bagi Anak Berkebutuhan Khusus - Nurhidayat Nurhidayat; Khaerul Wahidin; Muhammad Azka Maulana (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
Allah SWT created humans and jinn solely to worship Him and has no ally for Him as explained in His noble book, namely the Al-Quran Surah Az-Zariyat [51] : 56. When we worship to Allah, of course we need the knowledge because all the rules and theories contained in Islam are based on the knowledge. Even if we demand and gaining the knowledge, then it will be recorded as the value of the reward every time we do it. In addition, by demanding and gaining the knowledge, Allah will make it easy for us to take the path to heaven. Therefore, the obligation to study for every Muslims, both male and female, is a must, as well as children with special needs without any exception. Those children with special needs who have some limitations also have an obligation to study, because in the current phenomenon, there are still many children with special needs who don’t get the opportunity to undergo education. Therefore, the purpose of this study was to see how the Islamic religious perspective regarding the obligation to study for children with special needs. The method used in this study is a qualitative method which will produce a number of descriptive data. The data collection technique used is literature study where the sources obtained come from books, journals, articles, as well as the Qur'an and Hadith. The results of this study indicate that by studying, children with special needs can continue their lives as independent humans.